Valsartan alleviates the blood–brain barrier dysfunction in db/db diabetic mice. Issue 1 (1st January 2021) - Cai, Longxue; Li, Wenfeng; Zeng, Renqing; Cao, Zuohong; Guo, Qicai; Huang, Qi; Liu, Xianfa
ABSTRACT: Type 2 diabetes (T2D)-related neurological complication is the risk factor for neurodegenerative disorders. The pathological changes from T2D-caused blood–brain barrier (BBB) dysfunction plays a critical role in developing neurodegeneration. The hyper-activation of the Angiotensin II type 1 receptor (AT1R) in the brain is associated with neurovascular impairment. The AT1R antagonist Valsartan is commonly prescribed to control high blood pressure, heart failure, and diabetic kidney diseases. In this study, we investigated the beneficial effects of Valsartan in db/db diabetic mice and isolated brain endothelial cells. We showed that 2 weeks of Valsartan administration (30 mg/Kg body weight) mitigated the increased permeability of the brain-blood barrier and the reduction of gap junction proteins VE-Cadherin and Claudin 2. In human brain microvascular cells (HBMVECs), we found that Valsartan treatment ameliorated high glucose-induced hyperpermeability by measuring Dextran uptake and transendothelial electrical resistance (TEER). Furthermore, Valsartan treatment recovered high glucose-repressed endothelial VE-Cadherin and Claudin 2 expression. Moreover, Valsartan significantly suppressed the expressions of pro-inflammatory cytokines such as macrophage chemoattractant protein-1 (MCP-1) and interleukin-6 (IL-6) against high glucose. Mechanistically, Valsartan ameliorated high glucose-repressed endothelial cAMP-responsive element-binding protein (CREB) signaling activation. The blockage of CREB activation by PKA inhibitor H89 abolished the action of Valsartan, suggesting its dependence on CREB signaling. In conclusion, Valsartan shows a neuroprotective effect in diabetic mice by ameliorating BBB dysfunction. These effects of Valsartan require cellular CREB signaling in brain endothelial cells.